Constructing the Caribbean Court of Justice: How Ideas Inform Institutional Choices - Kocken, Joris; van Roozendaal, Gerda (European Review of Latin American and Caribbean Studies, 2012)
Abstract:The Caribbean Court of Justice (CCJ) is a relatively new legal institution in the Caribbean. This article explores the question of where this specific way of institutionalizing conflict resolution came from and in which way its success (or lack of it) can be accounted for. The authors analyse the support for and opposition to the CCJ found in four issues: economic progress, sovereignty, identity and trust. Their approach to institutionalization shows that only one of the four issues discussed – economic progress – has led to substantial and decisive support for the CCJ in its original jurisdiction as aCARICOM court. Lacking such economic drive, the other function of CCJ, which is becoming the successor of the British Privy Council as the shared regional appellate court, is still by and large withheld regional support. In general, the absence of common sovereignty, identity and trust continues to hamper regional cooperation in the Caribbean.Resumen: Construyendo la Corte de Justicia del Caribe: Cómo las ideas fundamentan las decisiones institucionalesLa Corte Caribeña de Justicia (CCJ) es una institución legal relativamente nueva en el Caribe. Este artículo explora la cuestión de dónde viene esta forma específica de institucionalizar la resolución de conflictos y de qué manera su éxito (o falta de ella) puede tomarse en cuenta. Los autores analizan el apoyo y la oposición a la CCJ encontrados en cuatro temas: el progreso económico, la soberanía, la identidad y la confianza. Su acercamiento a la institucionalización muestra que sólo uno de los cuatro temas tratados – el progreso económico – ha conducido a un apoyo sustancial y decisivo para la CCJ en su jurisdicción original como tribunal CARICOu. A falta de dinamismo económico, la otra función de la CCJ, la cual se convirtió en el sucesor del Consejo Privado británico como el tribunal de apelación regional compartida, sigue siendo en general el apoyo regional retenido. En general, la ausencia de soberanía común, la identidad y la confianza sigue obstaculizando la cooperación regional en el Caribe.